Korean traditional herbal formula Soshiho-tang attenuates memory impairment and neuronal damage in mice with amyloid-beta-induced Alzheimer's disease - Eunjin Sohn; Yu Jin Kim; Soo-Jin Jeong (Integrative Medicine Research)
Background: Soshiho-tang (SST), also known as Xiaochaihu-tang in China and Sho-saiko-to in Japan, is an Oriental herbal formula traditionally used to treat febrile diseases. Recently, several in vitro and in vivo studies have reported the anti-cancer, anti-liver disease, and anti-inflammatory activities of SST. However, there is little evidence of its effects on neurological diseases. We previously reported the inhibitory effects of SST on in vitro acetylcholinesterase (AChE) activation and amyloid-β (Aβ) aggregation, which are crucial hallmarks of Alzheimer's disease (AD). In the present study, we report that SST has preventive effects on memory impairment and neuronal cell changes in an Aβ-induced AD-like mouse model. Methods: Male mice underwent injection of Aβ aggregates and administered SST (500, 1,000, or 2,000 mg/kg/day) for 20 days. Behavioral tests (passive avoidance task [PAT] and Morris water maze [MWM] test) were conducted. Lastly, brain sections were obtained from sacrificed mice for quantitative analysis. Results: Intracerebroventricular (ICV) injection of Aβ aggregates significantly decreased the latency time in the PAT and MWM test compared to normal control. In contrast, SST administration markedly reversed the latency caused by Aβ injection. Additionally, our data revealed that SST-mediated improvements in memory impairment are related to its neuroprotective and anti-neuroinflammatory effects. On histological analysis, SST treatment protected neuronal loss and damage as well as microglial activation, and ameliorated amount of Aβ in brain of mouse model of AD. Conclusion: Our findings suggest that SST may be a promising candidate for the development of novel drugs for AD.